Assessment of four different media for the mass culture of Ceriodaphnia reticulata (Jurine) as a live fish feed (Journal of the Asiatic Society of Bangladesh, Science, 2014)
Experiments on the mass culture of Ceriodaphnia reticulata (Jurine) were carried out in aquarium water for 54 days with different media like cowdung (1.5g/L), pulse bran water (50g/L), poultry manure (0.45g/L) and snail faeces (faeces of six apple snails). All the media were fertilized by 50-100% of the initial amount of feed in every 7 days. About 100 individuals of C. reticulata were inoculated as starter in 50 litres of water (2 individuals/ml).The temperature of the media ranged from 24-30oC during study period. pH of the culture media varied i.e., 9.1 ± 0.40 in cowdung; 8.72 ± 0.73 in pulse bran water, 8.82 ± 0.72 in poultry manure and 7.5 ± 0.55 in snail faeces. The highest average population of C. reticulata was observed in cowdung (8.56 ± 4.11individuals/ml), moderate in poultry manure (4.21 ± 2.97 individuals/ml) and snail faeces (2.52 ± 3.01individuals/ml). The lowest growth of C. reticulata was recorded in pulse water (0.37 ± 0.69 individuals/ml). The culture media with cowdung as well as poultry manure and snail faeces were found to be useful for artificial mass production of C. reticulata. DOI: http://dx.doi.org/10.3329/jasbs.v39i2.17849 J. Asiat. Soc. Bangladesh, Sci. 39(2): 129-138, December 2013